Erectile Dysfunction among Nigerian Men with Diabetes: a Systematic Review - Adegoke Azeez, Taoreed; Olawale Ogunlayi, Sheriff; Ehizode Emuze, Martins; Chinedu Eguzozie, Emmanuel (Archives of Men’s Health, 2020)
Background Diabetes mellitus is a chronic metabolic disorder with multiple microvascular and macrovascular complications. Some of the complications of diabetes such as erectile dysfunction are a result of an interplay of both microvascular and macrovascular complications. Erectile dysfunction is the inability to achieve or sustain an erection adequate for satisfactory sexual activity. Erectile dysfunction is relatively common in men with diabetes yet there is a paucity of information on erectile dysfunction among Nigerian men with diabetes. Materials and Methods: Twelve studies on erectile dysfunction in Nigerian men with diabetes with a total sample size of 1777 fulfilled the eligibility criteria and were recruited into the systematic review. The International Index of Erectile Function (IIEF) questionnaire was used to assess erectile dysfunction in all the studies. Results: The prevalence of erectile dysfunction among Nigerian men with diabetes is 48.4-98.0%. The factors significantly associated with the presence of erectile dysfunction among Nigerian men with diabetes are longer duration of diabetes, poor glycaemic control, older age, peripheral arterial disease, autonomic neuropathy and obesity. Conclusion: The prevalence of erectile dysfunction among Nigerian men with diabetes is high. Close attention needs to be paid to glycaemic control in these patients to reduce the complications.